Evolution of Ferritin/ C-Reactive Protein (CRP)Ratio Inpatients of Iron Deficiency Anemia With orWithout Systemic Inflammation (IAHS Medical Journal, 2026)
Background: The diagnosis of Iron Deficiency Anemia (IDA) is complicated by inflammation, which causes ferritin, a crucial iron-storage indicator, to increase as an acute-phase reactant, obscuring the actual iron status. Simultaneously, inflammatory cytokines inhibit iron uptake and recycling. This results in "Functional iron deficiency" insufficient iron availability despite adequate reserves. To compare Ferritin/ CRP ratio among the patients with raised CRP and low CRP levels.Materials and methods: This Cross-sectional analytical study was conducted in the Department of Biochemistry, IAHS. The study was conducted from January 2024 to March 2025. 90 patients with Iron Deficiency Anemia (IDA) were selected by non-purposive sampling method. It includes 45 IDA patients with high CRP and 45 IDA patients with low CRP. Important variable of this study were Ferritin, CRP, Ferritin/CRP ratio, Hb, Transferrin saturation.Results: Systemic inflammation severely disrupts iron metabolism, causing functional iron deficiency characterized by low available iron and transferrin saturation despite suppressed ferritin, while increasing total iron-binding capacity. The Ferritin/CRP ratio strongly reflects this inflammation-driven iron dysregulation, showing meaningful positive links to improved iron availability, transferrin saturation and hemoglobin levels, alongside a negative association with TIBC. This ratio effectively identifies functional iron deficiency, outperforming ferritin alone by incorporating inflammatory status, demonstrating clinically useful diagnostic performance for distinguishing it from absolute deficiency. Therefore, the Ferritin/CRP ratio serves as a valuable integrated marker of inflammation mediated iron blockade and its resulting anemia.Conclusion: The Ferritin/CRP ratio serves a substantial clinical benefit by clarifying the diagnostic uncertainty related to impact of inflammation on iron status. It accurately diagnoses functional iron insufficiency, allowing more precise therapeutic targeting than relying solely on ferritin.IAHS Medical Journal Vol 8(2), December 2025; 10-14